A 3D progressive failure model for crushing simulations in composite structures. Issue 2 (4th March 2022) - Capasciutti de Oliveira, Sérgio Augusto; Vicente Donadon, Maurício
Abstract: A constitutive damage model is proposed in order to investigate the crushing response of crossply and 0 ° plies composite laminates, using a VUMAT subroutine implemented in ABAQUS/Explicit. This damage model predicts five failure modes commonly observed in unidirectional (UD) carbon fibres reinforced composite structures: fibre failure in tension, fibre failure in compression, matrix cracking in tension, matrix cracking in compression and in-plane shear failure. Its formulation is based on an energy framework which combines stress-based fracture mechanics and damage mechanics approaches within a unified way, enabling the prediction of the five failure modes aforementioned in terms of damage initiation and damage propagation. In this work a new fibre kink formulation is proposed taking into account the stresses degradation on the matrix fracture plane inside the kinking band. An experimental test campaing is proposed for verification of the numerical models. Additional comparisons between predictions obtained using the proposed model and experimental results taken from the open literature are also presented and discussed. An overall good correlation between numerical predictions and experimental data, taken from literature and in-house experimental results for wedge-shaped tip composite, was obtained.